Does brand attachment protect consumer–brand relationships after brand misconduct in retail banking? - Shimul, Anwar Sadat; Faroque, A.R.; Cheah, Isaac (2024)
Purpose: This research aims to examine the role of consumers' brand trust and attachment on advocacy intention before and after the occurrence of brand misconduct in retail banking. In addition, the influence of brand attachment on consumers' willingness to switch, advocate for and forgive brands is examined in a post-misconduct scenario. Design/methodology/approach: Data were collected through a self-administered online survey questionnaire. A total of 304 valid and usable responses from Australian participants were analysed using IBM SPSS 27.0. Findings: The findings reveal that brand attachment mediates the positive relationship between trust and advocacy intention. Furthermore, brand attachment (1) dilutes consumers' switching intention and (2) strengthens their willingness to forgive the bank after misconduct. Practical implications: Results suggest that retail banks should create strong brand attachments with their consumers. In addition to brand trust, brand attachment will generate greater advocacy intention among consumers. Moreover, practitioners in retail banking can leverage brand attachment to mitigate the negative impact of brand misconduct. Originality/value: To the best of the authors' knowledge, this study is the first to examine the impact of brand attachment on the consumer–bank relationship within the context of brand misconduct. The study is also unique in its analysis of the mediating role of brand attachment between brand trust and advocacy. This research further adds to the current literature by suggesting that strong and positive customer connections to the brand facilitate communication and marketing efforts after brand misconduct and that these are effective in maintaining consumer-bank relationship.